Agonism and allosterism: the pharmacology of the free fatty acid receptors FFA2 and FFA3 - Milligan, Graeme (Blackwell Publishing Ltd, 2009)
The free fatty acid receptors FFA2 and FFA3 are recently de-orphanized G protein-coupled receptors that share a group of short-chain free fatty acids as endogenous ligands. The expression of FFA2 and FFA3 by immune cells, in parts of the gastro-intestinal tract and by white adipocytes has suggested their potential as therapeutic targets in conditions including inflammation and obesity. However, although FFA2 and FFA3 display distinct structure–activity relationships for stimulation by short-chain free fatty acids, the overlap between these endogenous agonists and the lack of synthetic small molecule ligands that display selectivity between these two receptors has, until recently, hindered efforts to resolve their individual functions. Recently, chloro-α-(1-methylethyl)-N-2-thiazolylbenzeneacetamide has been described as an FFA2 selective ago-allosteric ligand, not only being a direct agonist but also acting as a positive allosteric modulator of the function of short-chain free fatty acids at FFA2. Mutation of a pair of key arginine residues near the top of transmembrane domains V and VII of both FFA2 and FFA3 eliminates the function of short-chain free fatty acids but is without effect on the direct agonist action of chloro-α-(1-methylethyl)-N-2-thiazolylbenzeneacetamide at FFA2, confirming the distinct nature of the binding site of the ago-allosteric regulator from the orthosteric binding site for free fatty acids. An understanding of structure–activity relationships for ligands related to chloro-α-(1-methylethyl)-N-2-thiazolylbenzeneacetamide is likely to provide greater insight into the mode of action and site of binding of this ligand, but further FFA2 and FFA3 selective ligands, preferably with higher potency/affinity, will be required to fully explore the physiological function of these receptors.